Mobilization of iron from ferritin: new steps and details. Issue 1 (20th December 2017) - La, A.; Nguyen, T.; Tran, K.; Sauble, E.; Tu, D.; Gonzalez, A.; Kidane, T. Z.; Soriano, C.; Morgan, J.; Doan, M.; Tran, K.; Wang, C.-Y.; et al.
Abstract : Much evidence indicates that iron stored in ferritin is mobilized through protein degradation in lysosomes, but concerns about this process have lingered, and mechanistic details of its aspects are lacking. Abstract : Much evidence indicates that iron stored in ferritin is mobilized through protein degradation in lysosomes, but concerns about this process have lingered, and the mechanistic details of its aspects are lacking. In the studies presented here, 59 Fe-labeled ferritin was induced by preloading hepatic (HepG2) cells with radiolabeled Fe. Placing these cells in a medium containing desferrioxamine resulted in the loss of ferritin- 59 Fe, but adding high concentrations of reducing agents or modulating the internal GSH concentration failed to alter the rates of ferritin- 59 Fe release. Confocal microscopy showed that Fe deprivation increased the movement of ferritin into lysosomes and hyperaccumulation was observed when lysosomal proteolysis was inhibited. It also resulted in the rapid movement of DMT1 to lysosomes, which was inhibited by bafilomycin. Ferrihydrite crystals isolated from purified rat liver/spleen ferritin were solubilized at pH 5 and 7 by GSH, ascorbate, citrate and lysosomal fluids obtained from livers and J774a.1 macrophages. The inhibition of DMT1/Nramp2 and siRNA knockdown of Nramp1 each reduced the transfer of 59 Fe from lysosomes to the cytosol; and hepatocyte-specific knockout of DMT1 in mice prevented the release of Fe from the liver responding to EPO treatment, but did not inhibit lysosomal ferritin degradation. We conclude that ferritin-Fe mobilization does not occur through changes in cellular concentrations of reducing/chelating agents but by the coordinated movement of ferritin and DMT1 to lysosomes, where the ferrihydrite crystals exposed by ferritin degradation dissolve in the lysosomal fluid, and the reduced iron is transported back to the cytosol via DMT1 in hepatocytes, and by both DMT1 and Nramp1 in macrophages, prior to release into the blood or storage in ferritin.